Banking Selection Criteria among Millennials: Insights from Islamic and Conventional Banks - Rama, Ali; Wiranata, Suhenda (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah, 2023)
The increasing number of millennials presents an enticing market opportunity for business. Understanding their preferences is the key to attracting their sympathy and interest. Thus, this study aims to analyze banking selection criteria for Islamic and conventional banks among the young generation. A group of students represents the millennial group in this study. Data is collected through questionnaire instruments, and factor analysis is employed to capture millennials' preference for banking. The finding highlights a relatively lower level of knowledge and awareness among millennials regarding the products and services offered by Islamic banks. Interestingly, among them, an inverse relationship exists between the criteria for selecting Islamic and conventional banks. Factors associated with banking preference among millennials are managerial performance and service quality, religiosity, recommendations, and finances. This study provides valuable insights for banking industry players, enabling them to understand millennial banking preferences better and formulate suitable marketing strategies.JEL Classification: G21, G32, D81How to Cite:Rama, A., & Wiranata, S. (2023). Banking Selection among Millennials: Insights from Islamic and Conventional Banks. Signifikan: Jurnal Ilmu Ekonomi, 12(2), 341-354. https://doi.org/10.15408/sjie.v12i2.35104.